Synthesis of tricyclic marine alkaloids, cylindricines, lepadiformines, fasicularin, and polycitorols : a recent update - Kaga, Atsushi (2019)
Cylindricines, lepadiformines, and fasicularin are tricyclic marine alkaloids bearing perhydropyrrolo- and pyrido[2,1-j] frameworks having divergent chemical functionalities. They have been isolated from marine tunicates over the last two decades and found to have a range of cytotoxicity such as DNA-alkylating ability. Recently, polycitorols have emerged as a new member of this alkaloid family. Their unique structural features and biological activities have intrigued many researchers and challenged them in their synthesis. This review describes recent syntheses of the tricyclic alkaloids based on key synthetic approaches.